МІЖНАРОДНА НАУКОВА ПУБЛІКАЦІЯ: ЕФЕКТИВНА НАЗВА - Чорновол-Ткаченко, Ольга Олександрівна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2015)
The article makes an attempt at claiming attention of scientists who are planning to рІасе results of their research in intemational reviewed scientific periodicals to the role of the scientific paper title. The paper reviews basic characteristics and functions of а scientific paper title in the frames of intemational scientific communication at present. The linguodidactic research results in а list of guidelines for an effective scientific paper title.